Ensemble-Induced Strong Light-Matter Coupling of a Single Quantum Emitter - Schutz, S.; Schachenmayer, J.; Hagenmuller, D.; Brennen, G. K.; Volz, Thomas; Sandoghdar, Vahid; Ebbesen, T. W.; Genes, Claudiu; Pupillo, G. (Physical Review Letters, 2020)
We discuss a technique to strongly couple a single target quantum emitter to a cavity mode, which is enabled by virtual excitations of a nearby mesoscopic ensemble of emitters. A collective coupling of the latter to both the cavity and the target emitter induces strong photon nonlinearities in addition to polariton formation, in contrast to common schemes for ensemble strong coupling. We demonstrate that strong coupling at the level of a single emitter can be engineered via coherent and dissipative dipolar interactions with the ensemble, and provide realistic parameters for a possible implementation with SiV- defects in diamond. Our scheme can find applications, amongst others, in quantum information processing or in the field of cavity-assisted quantum chemistry.
CRIS-Team WoS Importer:2020-04-10